The Adjuvants Have a Key Role Improving the Protection and Immune Response Induced by Recombinant Protein Vaccine Against Infectious Salmon Anemia Virus Isav in Atlantic Salmon - Spencer-Ossa, E; Sandino-Garcia, A; Imarai-Bahamonde, C; Acuna-Castillo, C; Reyes-Cerpa, S; Cortez-San Martin, M; Toro-Ascuy, D; Cottet-Bustamante, L (Academic Press, 2013)
Sin Resumen Disponible